THE EFFECT OF INDUSTRIAL WORK PRACTICES AND WORK MOTIVATION ON WORK READINESS IN CLASS XII SMK NEGERI 1 KALIANDA - Karyaningsih, RR Ponco Dewi; Rachmadania, Rizki Firdausi; Ananda, Novia (Faculty of Economics and Business, Universitas Negeri Jakarta, 2021)
This study aims to determine whether there is an effect of industrial work practices and work motivation on the work readiness of class XII students of SMK Negeri Jakarta. The research method used is a quantitative method. The population in this study amounted to 469 students with a sample of 150 students. Data on work readiness (Y), industrial work practices (X1), and work motivation (X2) are primary data using a Likert scale. Methods of data collection by using a questionnaire. The data analysis technique used is descriptive analysis and multiple linear regression analysis with the help of SPSS 25.0 program. The results of this study are that there is a positive and significant effect of industrial work practices on work readiness of 5.950 > 197623, work motivation on work readiness of 0.862 > 1.97623 and F count of 54,